2021
DOI: 10.3390/en14185895
|View full text |Cite
|
Sign up to set email alerts
|

Densification of Wood—Influence on Mechanical and Chemical Properties when 11 Naturally Occurring Substances in Wood Are Mixed with Beech and Pine

Abstract: The need to increase the use of renewable biomasses for energy supply, such as fuel pellets is significant. However, different types of biomasses have different mechanical properties to be pelletized, which entails a limitation in available raw materials for pellet producers. Within this study eleven different pure substances from biomasses were separately mixed with European beech and Scots pine, to identify its impact on the densification process. Beech and pine pellets were used as control materials against… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…However, as seen in Table 4, bark's bulk density is lower than hydrochar and ash. As seen in Table 5, the power need and temperature during pelletization are lower for the mix with bark, meaning that bark is a lubricant in the pelleting process, which is consistent with other studies [33]. So, it is likely that the pellets with bark can increase their bulk density by increasing the presslength slightly.…”
Section: Pelletizing and Pellet Propertiessupporting
confidence: 88%
See 2 more Smart Citations
“…However, as seen in Table 4, bark's bulk density is lower than hydrochar and ash. As seen in Table 5, the power need and temperature during pelletization are lower for the mix with bark, meaning that bark is a lubricant in the pelleting process, which is consistent with other studies [33]. So, it is likely that the pellets with bark can increase their bulk density by increasing the presslength slightly.…”
Section: Pelletizing and Pellet Propertiessupporting
confidence: 88%
“…When it comes to durability, it is clear that adding bark to hydrochar and ash creates a more durable pellet (see 6). Likely, the reason behind an increase in the mechanical quality of the bark-blended pellets can be attributed to lignin; however, these bondings are not tested, and extractives or carbohydrates have been found to generate even better bondings than lignin [33], so further studies are needed. The pellets produced based on this study using the two blends have met the ISO standards regarding moisture and bulk density, and for 45/10/45 also durability (BD800+ (>900 kg/m 3 ), DU95.0− (<90%), and DU95.0 (≥95%) and M08 (moisture ≤ 8%)) (See Figure 5).…”
Section: Pelletizing and Pellet Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analyzed pellets, the destructive force oscillated in the range from 601.53 to 788.71 N. The addition of fir sawdust from coniferous trees during the production process of pellets from waste biomass of sunflower and tobacco improved the strength parameters of the tested pellets [33]. Analyzing the destructive force for pellets made of coniferous and deciduous sawdust and beech wood, it was found that 166 N to 654 N was needed to destroy different types of pellets [38]. The mechanical strength of pellets produced from straw increases as a result of the use of an additive in the form of coniferous sawdust during the production process [39].…”
Section: Measurement Of Mechanical Propertiesmentioning
confidence: 99%
“…The mechanical properties of pellets depend in particular on the type of materials used for their production, the water content, the chemical composition of raw materials, and the addition of an adhesive [37,38]. Pellets made of raw materials containing large amounts of starch are characterized by greater resistance to mechanical damage.…”
Section: Measurement Of Mechanical Propertiesmentioning
confidence: 99%